VD_FINDINFO Jug / 2012 / 39 vom 18. Januar 2012 - VD Tribunal cantonal (2012)
RÉSILIATION ABUSIVE, GRATIFICATION, ACTION REMISE AU SALARIÉ | 322d CO, 336 al. 1 CO, 336 al. 1 let. c CO, 336 CO, 336b al. 1 CO, 336b al. 2 CO, 336b CO